Shelter from the Holocaust Rethinking Jewish Survival in the Soviet Union - Grossmann, Atina; Edele, Mark; Fitzpatrick, Sheila (Wayne State University Press, 2018)
Shelter from the Holocaust came to fruition as the result of the opening of formerly classified Soviet and Polish archives, determined efforts to interview the last remaining Holocaust survivors, and the growing interest in the histories of displaced persons and migration. Scholars of eastern European history and Holocaust studies, as well as those with an interest in refugee and migration issues, will appreciate this overview.